Opozycja antysystemowa we współczesnych państwach totalitarnych - rzeczywistość czy abstrakcja? - Kontowska, Angelika (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This article analyses the problem of anti-systemic opposition’s existence in a totalitarian state. Different concepts concerning the genesis of totalitarianism as well as the features of this system were presented in the paper. Then, the idea of the opposition in a totalitarian state was defined. At the same time, it was emphasized that defining the oppositional quality in a democratic and totalitarian state is completely disparate. Next, an analysis of anti-systemic opposition’s occurrence in the states such as the Republic of Cuba and the Democratic People’s Republic of Korea was made. This analysis helped to answer the question concerning the conditions which must exist in a totalitarian state so that the anti-systemic opposition could appear.